Indian classical dances: ekam sat viprah bahudaa vadanti - Narayan, Shovana (Gurgaon Shubhi, 2022)
India is perhaps the only country with eight recognized classical dance forms and these Indian Classical Dances have captured the imagination of people all over the world, Steeped into spiritualism, they are living practices connection the past and present. Its pulsating spirit ensures a bright future. This book provides with abundance of detailed information combined with in-depth study of the magnificence of techniques, presentations, also incorporating details on costume and music in each of the eight classical forms. It also provides a critical perspective on the evolution of each dance style as a result of regionalization and the subsequent reconstruction of few of the dance forms. Many questions regarding applicability of Natyashastra to all dance forms without exception in regard to salient features and presentation techniques are answered in this book. This book blends-wide ranging information with analysis and wisdom and is a must for simple readers as well as serious students of music and dance.
Keywords: Classical dance